The black reparations project: a handbook for racial justice - Darity, William A. Jr.; Mullen, A. Kirsten; Hubbard, Lucas (University of California Press, 2023)
This groundbreaking resource moves us from theory to action with a practical plan for reparations. A surge in interest in black reparations is taking place in America on a scale not seen since the Reconstruction Era. The Black Reparations Project gathers an accomplished interdisciplinary team of scholars—members of the Reparations Planning Committee—who have considered the issues pertinent to making reparations happen. This book will be an essential resource in the national conversation going forward. The first section of The Black Reparations Project crystallizes the rationale for reparations, cataloguing centuries of racial repression, discrimination, violence, mass incarceration, and the massive black-white wealth gap. Drawing on the contributors’ expertise in economics, history, law, public policy, public health, and education, the second section unfurls direct guidance for building and implementing a reparations program, including draft legislation that addresses how the program should be financed and how claimants can be identified and compensated. Rigorous and comprehensive, The Black Reparations Project will motivate, guide, and speed the final leg of the journey for justice